Inequality and participation in Chile: Does multidimensional poverty affect electoral participation? - Riquelme Arriagada, Alberto (2020)
Electoral participation in Chile as in the world constitutes a broad field of study, however, research that associates poverty with participation in elections has focused only on the one-dimensional measurement of it, without considering its multidimensional conception. Searching to complete that gap is analyzed the communal poverty rates and the presidential elections in Chile carried out by voluntary vote, in order to answer, does multidimensional poverty affect electoral participation? To achieve this, the method of ecological inference is used with which to reach individual conclusions from aggregated information. It is argued that among people in poverty the tendency to abstain is greater than among those who are not in this condition, thus generating unequal electoral participation. The main conclusions are that the participation rates among the poor do not exceed 38.75%, while among the non-poor the tendency to vote is higher.